SỬ DỤNG MÔ HÌNH TOÁN TỐI ƯU TRONG XÁC ĐỊNH CƠ CẤU SỬ DỤNG ĐẤT SẢN XUẤT NÔNG NGHIỆP HỢP LÍ XÃ GIÁO LIÊM – HUYỆN SƠN ĐỘNG – TỈNH BẮC GIANG - Giang, Lê Thị; Thủy, Đoàn Thanh (Vietnam Journal of Science and Technology, 2012)
APPLYING OPTIMAL MODEL FOR DEFINING SUITABLE AGRICULTURAL LAND USE STRUCTURE Case study: Giao Liem commune, Son Dong district, Bac Giang province, Vietnam The research projects is conducted in Giao Liem commune, Son Dong district, Bac Giang province in 2009. Applying optimal model to propose the plan of logical using agricultural land in the locality which may promote the development of agricultural is the research’s objective. By interviewing 50 households in the commune, economic efficiency of some model production in the town was evaluated such as: spring rice, summer rice, corn, peanuts, cassava, beans, sweet potatoes, vegetables, litchis and pig rising. After that, building multi-objective optimization was proceeded with 2 main objects: the first objective function shows the maximum total revenue, then the problem would be solved with the objective function is to achieve the highest net income while ensuring total income at the highest level could be achieved. With those objective functions, setting the limit conditions for variables of the function, entering data and running the programs on the Solver Module, the result was the structure of area of using land models to ensure the 2 optimal objectives above.